Double‐tuned 31P/1H human head array with high performance at both frequencies for spectroscopic imaging at 9.4T. Issue 2 (30th January 2020) - Avdievich, Nikolai I.; Ruhm, Loreen; Dorst, Johanna; Scheffler, Klaus; Korzowski, Andreas; Henning, Anke
Abstract : Purpose: To develop a robust design of a human head double‐tuned 31 P/ 1 H array, which provides good performance at both 31 P and 1 H frequencies for MR spectroscopic imaging at 9.4T. Methods: Increasing the number of surface loops in a human head array improves the peripheral signal‐to‐noise ratio (SNR), while the central SNR doesn't substantially change. High peripheral SNR can contaminate MR spectroscopic imaging data at both 1 H and 31 P frequency. To minimize this effect, we limited the number of elements in the 31 P array to 10, i.e., 8 transceiver surface loops circumscribing the head and 2 receive "vertical" loops placed at the superior location. The 1 H‐portion of the array also consists of 10 elements, i.e., 8 transceiver surface loops circumscribing the head and 2 transceiver "vertical" loops at the superior location of the head. Both the 31 P array and 1 H array are placed in a single layer at the same distance to the head, which provides high loading and, thus, a good performance for both arrays. Results: Transmit efficiency of the 1 H‐portion of the double‐tuned array was very similar to that of the single‐tuned arrays of similar size. Also, addition of the cross‐loops substantially improved the brain coverage. Conclusion: We developed a novel 31 P/ 1 H double‐tuned array for MR spectroscopic imaging of a human brain at 9.4T. Placing both 31 P and 1 H loops in a single layer provides for high transmit efficiency at both frequencies without compromising SNR near the brain center at the 31 P‐frequency. Addition of the cross‐loops at the superior location improves the brain coverage.